Translation termination mutations analysis using the protein truncation test on exon11A of the BRCA1 gene in female breast cancer patients of Pahang, Malaysia - Alattraqchi, Ahmed G.; Mustafa Mahmoud, Mohammed Imad Al-Deen; Salih, Falah; Amjad, Nasser Muhammad; Maung, Khin Maung; Kaderi, Mohd Arifin; Azzubaidi, Marwan Saad (Design for Scientific Renaissance, 2012)
Breast cancer is one of the commonest cancers in Malaysian females. Searching for a molecular link between breast cancer, early onset gene 1 (BRCA1) mutations and the development of early onset breast cancer has been of major interest over the past two decades. BRCA1 gene is located on chromosome 17 and known as a tumour suppressor gene maintaining genomic integrity to prevent uncontrolled proliferation of cells. Previous studies have found several translation termination mutations that led to the formation of truncated protein. The aim of this study was to investigate the presence of detectable germ-line translation termination mutations within nucleotide 790 until 1950 of the coding region of BRCA1 gene. Subsequently we aim to contribute any detected mutations to the Breast Cancer Information Core (BIC). Information regarding age and family history of breast or ovarian cancer were obtained from each patient and control. DNA extracted from the blood samples was screened for the presence of translation termination mutations in Exon 11 (segment A) of the BRCA1 gene by the Protein Truncation Test (PTT). The PTT analysis did not detect any truncations, which indicates that there were no translation termination mutations in the investigated BRCA1 gene segment. These findings were subsequently verified by DNA sequencing analysis. Hence, this study concludes that there were no translation termination mutations within the studied segment of the BRCA1 gene in the studied population. Therefore we suggest other studies regarding other segments of Exon 11 and other Exons of the BRCA1 gene in addition to other types of mutations for future studies.